Integrasi Model Kano ke Dalam QFD untuk Mengoptimalkan Kualitas Perguruan Tinggi di Provinsi Riau - Hafidzah Nurjannah; Desy Mardianty (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2019)
Higher Education has become a need for formal education as a strategic sector which is expected to produce quality intellectual graduates who are competitive. The competitive situation among universities requires educational institutions to pay attention to the quality of their education so that they are able to excel in the competition. To be able to compete, universities must improve their quality by providing attributes that are a priority for student needs. The purpose of this study is to optimize the quality of Private Universities in Riau Province by providing several technical responses. The population in this study were all active students of Private Universities in Riau Province and the total sample of 397 respondents using probability sampling techniques. This study uses the Kano Model and the Quality Function Deployment (QFD) approach as an integration tool that can help collect student voices as customers (VoC) and produce a priority matrix of needs and technical responses in the form of House of Quality (HoQ). The results of this study found 7 (seven) priority priorities for students, including the online KRS filling process that is very easy for students, academic information easily obtained, fast, and accurate, academic administration staff are reliable / responsive in providing services, adequate health facilities, Adequate library facilities (books, proceeding journals, and articles), Easy internet access, and adequate computer labor. From this research, Private Universities can take several steps to optimize quality such as improving internet facilities, monitoring academic rules, and monitoring the learning process. Keywords : Kano Model, House of Quality (HoQ), Quality Function Deployment (QFD), Quality